What about the baby? : some thoughts on the art of fiction - McDermott, Alice (Farrar, Straus and Giroux, 2021)
"A collection of essays, lectures, and observations on the art of writing fiction from Alice McDermott, winner of the National Book Award and unmatched "virtuoso of language and image" (Rebecca Steinitz, The Boston Globe)"--